Editor’s Message - Verde, Linda (Operating Room Nurses Association of Canada Journal, 2024)
Hello! Welcome to the first issue of the relaunched ORNAC Journal! I am delighted to be part of this step on the ORNAC journey and look forward to working with the Editorial Board, reviewers, and authors to bring you leading-edge ideas, processes, and best practices. We are living in an exciting time, full of transitions and changes that require agility and resilience. From what I see, that is what you perioperative nurses do best.